Circadian rhythm and joint stiffness/destruction in rheumatoid arthritis. (October 2015) - Yoshida, Kohsuke; Hashimoto, Teppei; Sakai, Yoshitada; Hashiramoto, Akira
In patients with rheumatoid arthritis, joint stiffness and pain levels reach peak in the morning, which is a characteristic symptom with diurnal fluctuation. In human, several types of hormone secretion, cytokine and antibody production are accelerated during night time as compared with those of day time, and these immune systems are partially controlled by circadian clock genes that regulate circadian rhythm. In this review, we focus on the interaction between circadian clock genes, immune system and the pathogenesis of rheumatoid arthritis.